Asthma and allergic rhinitis associate with the rs2229542 variant that induces a p.Lys90Glu mutation and compromises AKR1B1 protein levels. Issue 8 (25th May 2018) - García‐Martín, Elena; Sánchez‐Gómez, Francisco J.; Amo, Gemma; García Menaya, Jesús; Cordobés, Concepción; Ayuso, Pedro; Plaza Serón, M. Carmen; Blanca, Miguel; Campo, Paloma; Esguevillas, Gara; Pajares, María A.; G. Agúndez, José A.; et al.
Abstract: Asthma and rhinitis are two of the main clinical manifestations of allergy, in which increased reactive oxygen or electrophilic species can play a pathogenic role. Aldose reductase (AKR1B1) is involved in aldehyde detoxification and redox balance. Recent evidence from animal models points to a role of AKR1B1 in asthma and rhinitis, but its involvement in human allergy has not been addressed. Here, the putative association of allergic rhinitis and asthma with AKR1B1 variants has been explored by analysis of single‐strand variants on the AKR1B1 gene sequence in 526 healthy subjects and 515 patients with allergic rhinitis, 366 of whom also had asthma. We found that the rs2229542 variant, introducing the p.Lys90Glu mutation, was significantly more frequent in allergic patients than in healthy subjects. Additionally, in cells transfected with expression vectors carrying the wild‐type or the p.Lys90Glu variant of AKR1B1, the mutant consistently attained lower protein levels than the wild‐type and showed a compromised thermal stability. Taken together, our results show that the rs2229542 variant associates with asthma and rhinitis, and hampers AKR1B1 protein levels and stability. This unveils a connection between the genetic variability of aldose reductase and allergic processes. Abstract : The association between allergic rhinitis and asthma and aldose reductase ( AKR1B1 ) variants was explored in a cohort of Spanish healthy and allergic subjects. The frequency of the rs2229542 variant coding for the p.Lys90Glu mutation was higher in allergic subjects. This mutant form displayed weaker anti‐inflammatory effects than the wild type in transfected cells, was expressed at lower levels and presented reduced thermal stability.